Enhancement of the genotoxicity of benzo[a]pyrene by arecoline through suppression of DNA repair in HEp-2 cells. (June 2016) - Huang, J.L.; Lu, H.H.; Lu, Y.N.; Hung, P.S.; Lin, Y.J.; Lin, C.C.; Yang, C.C.; Wong, T.Y.; Lu, S.Y.; Lin, C.S.
Abstract: The International Agency for Research on Cancer lists the principal component of betel quid (BQ), the areca nut, and that of cigarette smoke, benzo[a]pyrene (BaP), as Group 1 carcinogens. Epidemiological studies have shown that coexposure of BQ and cigarette smoke markedly increases the risk of cancer. We previously demonstrated that arecoline, the most abundant alkaloid in the areca nut, inhibits nucleotide excision repair through the repression of p53 activity. To investigate the combined potency of arecoline and BaP in carcinogenesis, we treated human epithelial HEp-2 cells with subcytotoxic doses of arecoline and BaP, alone or in combination, and examined the effects on DNA damage and repair. When exposed for 24 h, BaP enhanced DNA repair and p53 transactivation activity. However, these enhancements were suppressed through concurrent treatment of the cells with arecoline. Using a Comet assay, we found that extended exposure to arecoline and BaP caused moderate-to-severe DNA damage in 60% of the cells. Expression of the XPD helicase was transcriptionally suppressed by 1 week of treatment with BaP. Our studies have revealed potential targets in the DNA repair pathway that are affected by BQ and tobacco components, as well as the effect of these components on carcinogenesis. Graphical abstract: Highlights: BaP enhances nucleotide excision repair (NER) and p53 transactivation activity in HEp-2 cells. Enhancement of DNA repair by BaP is suppressed by arecoline coexposure. Expression of the critical helicase of NER, XPD, was transcriptionally suppressed by long-term treatment with BaP. Combination of low doses of arecoline and BaP impairs DNA repair and results in severe DNA damage.